Pengaruh Kualitas Produk, Harga Dan Pelayanan Terhadap Pengambilan Keputusan Pembelian Batako Di Tb. Karya Mandiri - Rizqi, Angguliyah; Alie, R. M Mahrus; Ghofur, Abdul (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2023)
This research was conducted to determine the influence of product quality, price and service on decision making to purchase bricks at the Pt. Building Store. Independent Work. This study uses a quantitative approach. The sampling method used was simple random sampling with 80 samples. The type of data used in this research is primary data and secondary data in the form of questionnaires. The data analysis used in this research is classical assumption testing, multiple linear regression and hypothesis testing with the help of SPSS. The results of the research prove that product quality (x1), price (x2), and service (x3) have a positive and significant effect on purchasing decisions (Y). and overall the third variable simultaneously influences purchasing decisions at TB. Independent Work.